2013
DOI: 10.1039/c3ra40818c
|View full text |Cite
|
Sign up to set email alerts
|

Parameters in preparation and characterization of cross linked enzyme aggregates (CLEAs)

Abstract: Parameters in preparation and characterization of cross linked enzyme aggregates (CLEAs)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
141
0
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(152 citation statements)
references
References 170 publications
(202 reference statements)
3
141
0
8
Order By: Relevance
“…Talekar et al (2012) stabilized alpha-amylase from Bacillus amyloliquefaciens immobilized using (NH4)2SO4. As the concentration of this salt increased the enzyme activity also increased.…”
Section: Formulation Of Concentrated Metabolic Liquid With Cutinolytimentioning
confidence: 99%
“…Talekar et al (2012) stabilized alpha-amylase from Bacillus amyloliquefaciens immobilized using (NH4)2SO4. As the concentration of this salt increased the enzyme activity also increased.…”
Section: Formulation Of Concentrated Metabolic Liquid With Cutinolytimentioning
confidence: 99%
“…In the case of CLEA-β-SPI-12, a small shift to lower temperature (approximately 5 °C) of the maximum activity temperature was observed. It was expected that optimal pH and temperature of enzymes immobilized as CLEAs were shifted because covalent bonds established between amino groups of the enzyme and glutaraldehyde, changing the microenvironment and the conformational flexibility of the enzyme [49]. Talekar et al [72] reported a shift to higher temperature (around 15 °C) for β-amylase from Bacillus amyloliquefaciens after immobilization by CLEA technique.…”
Section: Effects Of Ph and Temperature On The Activity And The Stabilmentioning
confidence: 99%
“…It was expected that optimal pH and temperature of enzymes immobilized as CLEAs were shifted because covalent bonds established between amino groups of the enzyme and glutaraldehyde, changing the microenvironment and the conformational flexibility of the enzyme [49]. Talekar et al [72] reported a shift to higher temperature (around 15 °C) for β-amylase from Bacillus amyloliquefaciens after immobilization by CLEA technique. However, Mafra et al [58] a small shift to lower temperature (approximately 5 • C) of the maximum activity temperature was observed.…”
Section: Effects Of Ph and Temperature On The Activity And The Stabilmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach provided a simple strategy for obtaining excellent enzyme immobilization rate and desired stability for various biotechnological applications 7,8 . Moreover, glutaraldehyde was also exploited for preparing crosslinked enzyme aggregates (CLEAs) mainly in case of enzymes that have low density of surface reactive groups and therefore may pose problem to obtain a final solid catalyst 9,10 . The process of CLEAs formation involves the treatment of enzymes immobilized on supports that are non-reactive to glutaraldehyde in order to prevent enzyme leakage followed by the crosslinking of enzymes adsorbed on aminated supports.…”
Section: Fig 1: Chemical Properties Of Glutaraldehydementioning
confidence: 99%